Birds of a song sing together: adaptive choices in the use of shared vocalizations that indicate age - Magdaleno, Francisco R.; Zaratzian, Devin; Paladini-Colon, Ginnes; Jessum, Anya R.; O’Loghlen, Adrian L.; Rothstein, Stephen I. (Frontiers in Psychology, 2025)
The study of non-human animals that are vocal learning, which is the ability to alter the structure of vocalizations, has provided important insights into our understanding of the evolution and development of vocal communication and language. Of particular interest is vocal convergence where individuals learn the vocalizations shared by their social group. Although the development of shared vocalizations has received extensive study across vocal learning species, less attention has been given to the use of these learned signals, especially whether individuals stress the expression of vocalizations that signal high status and deemphasize those that do not. Previous field and captivity studies of Brown-headed Cowbirds (Molothrus ater) show that males 2 years old or older have greater levels of song type sharing than 1 year old males and that females are more sexually stimulated by shared song types than by the non-shared types that occur mostly in the repertoires of yearlings. In this study, we observed males at least 2 years old singing in experimentally paired matches with another male or female conspecific to determine whether they preferentially used some song types in their repertoires and whether preferences were based on shared songs that indicate male age. Data on over 5,000 songs by 12 males showed that males did not use song types randomly. The most frequently used song types directed to both males and females were types shared with the most other males. This was the case whether males or song types were the unit of analysis, clearly demonstrating that this species emphasizes vocalizations that signal high quality (an age of 2 years or more) and therefore optimizes the use of what it has learned. These results support the hypothesis that selection can favor stable presentation of shared vocalizations across social contexts because age-revealing information in vocalizations that require learning significantly improves the accuracy of age assessment, which in many species is typically based on maturational changes that occur with aging.